Addressing the challenges of reoperative robotic-assisted sacrocolpopexy - Wilson Lin; Nitya Abraham (International Brazilian Journal of Urology)
ABSTRACT Sacrocolpopexy is the gold-standard repair for apical pelvic organ prolapse (POP). However, over half of women with POP who undergo the surgery experience recurrence, particularly those with higher preoperative stage, younger age, and greater body weight. We address the challenges of repairing recurrent POP in a patient with a prior transabdominal mesh sacrohysteropexy.